The Colourful Days of 'Primitive Pan' - Unknown (Express)
The article discusses the Arima steelband, Colgate's Melodians which is making preparations to celebrate their 20th anniversary this year. A brochure will relay the history of the panside which was founded by Ivan Henry in May 1953 in the days of 'primitive pan'. Henry reminisces of steelband involvement , when the pan was held up in the air and played with one stick without a rubbertip.
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History; Steel band music -- Trinidad and Tobago -- History; Steel drum (Musical instrument) -- Trinidad and Tobago